The Dilemma of Public E-procurement in Costa Rica: Case on the Duality of Technological Platforms and Implementation Models. Issue 2 (November 2015) - Barahona, Juan Carlos; Elizondo, Andrey M; Santos, Manuel
Due to its characteristics, size and impact, e-procurement has a strategic importance for public administration, since its implementation necessarily crosses many institutional barriers and paradigms of many public managers. Many nations around the world are developing or revamping their National Public e-Procurement Systems. E-procurement brings a set of new rules and dynamics that create ways of doing business with the State in a totally different fashion, with a whole new and bigger set of participants, new incentives and a radically different cost structure. This case describes the experience of Costa Rica in implementing two different approaches for national e-procurement and the implications for public policy, e-government strategy and business development. Costa Rica has become an interesting laboratory for the world, since both approaches are coexisting and operating separately. Nevertheless, the country seeks to maintain a single e-procurement platform. The choice of either one of the platforms will bring serious organizational, economic, technological and political consequences for the government. We used multiple data collection methods. The data were collected from 2009 to 2012 from primary sources, studies, consulting work, official documents and the written press. Lessons drawn can be extended to other e-government ventures.